RANCANG BANGUN PEMANFAATAN ALIRAN TANDON AIR GEDUNG BERTINGKAT SEBAGAI PEMBANGKIT LISTRIK MIKRO HIDRO - Barus, Soraya; Aryza, Solly; Wibowo, Pristisal; Anisah, Siti; Hamdani, Hamdani (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2020, 2021)
The irrigation system in multi-storey buildings only has an automatic filling system for the water reservoir, the water flow from this reservoir is less than optimal in its utilization. Utilization of reservoir water output is a source of electrical energy that is easily utilized as renewable energy in micro-hydro power plants as an alternative solution to reduce the financing of monthly electricity payments. From the results of research and understanding, therefore the authors make a prototype micro hydro power plant by utilizing the reservoir water output in a multi-storey building. From the measurement results, the scale of comparison between the  prototype and its original form is 1: 5. From the testing of the tool, the results obtained from a height of 1.5 meters with a water discharge of or   capable of turning a water turbine that has been coupled with a DC generator of electrical energy generated by the generator is a voltage of 11.56 volts with a current of 0.05 A and the charging time for the lithium-ion battery is 2.5 hours or 2.5 hours and the length of time using the battery to load (lights) is for 2 , 4 hours or 2.4 hour. From the measurement results, the water pressure is 15,000 Pa or 0.15 bar, the water flow velocity is 5.29 m / s. The power generated from the prototype PLTMH 0.5 Watt.